THE TUDOR DYNASTY: POWER, POLITICS, AND RELIGION - Fayoza Xidirova G’ulom qizi; Ne’matova Madina Baxtiyor qizi (TADQIQOTLAR, 2025)
Annotation The  Tudor  dynasty  (1485–1603)  was  one  of  the  most  influential  periods  in English history. Beginning with Henry VII and ending with Elizabeth I, the Tudors established a strong monarchy, centralized government, and a new national identity. Their reign was marked by major political, religious, and cultural changes — from the Reformation  initiated  by  Henry  VIII  to  the  Elizabethan  Golden  Age.  The  Tudors transformed England into a powerful and unified nation that laid the groundwork for modern Britain.